2003
DOI: 10.1046/j.1540-8175.2003.03086.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approach to Measure Myocardial Performance Index: Pulsed‐Wave Tissue Doppler Echocardiography

Abstract: A simple, reproducible, noninvasive myocardial performance index (MPI) for the assessment of overall cardiac function has been described previously. The purpose of this study was to compare the MPI obtained by pulse Doppler method with the MPI obtained by tissue Doppler echocardiography (TDE) in normal subjects and patients with dilated cardiomyopathy (DCMP). Fifteen patients with DCMP and 15 healthy subjects were included. In order to calculate MPI by TDE, isovolumetric contraction (IVCT), relaxation time (IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
74
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 17 publications
5
74
1
Order By: Relevance
“…It is reported that the normal value of TDI Tei index range from 0.29-0.36. 11,16,18 The present study illustrates that TDI Tei index is higher in hypertensives, and more prominent in LVH group, but E/A shows no difference between NLVH and LVH groups, which suggests that TDI Tei index is a sensitive parameter for evaluation of global ventricular function before developing ventricular hypertrophy. The present study also supports the opinion that systolic dysfunction coexists with diastolic dysfunction in hypertensives.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…It is reported that the normal value of TDI Tei index range from 0.29-0.36. 11,16,18 The present study illustrates that TDI Tei index is higher in hypertensives, and more prominent in LVH group, but E/A shows no difference between NLVH and LVH groups, which suggests that TDI Tei index is a sensitive parameter for evaluation of global ventricular function before developing ventricular hypertrophy. The present study also supports the opinion that systolic dysfunction coexists with diastolic dysfunction in hypertensives.…”
Section: Discussionmentioning
confidence: 46%
“…Tei index was reported to be simple, reproducible and independent of HR and blood pressure. 25 Tissue Doppler imaging Tei index was used to evaluate LV function in patients with dilate cardiomyopathy, 16 myocardial infarction 18 and hypertension. 11 In those disease states, Tei index was found to be higher than in normal subjects, and TDI Tei index correlated well with traditional Tei index.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[27] Thus, TDI-derived MPI serves more reliable global cardiac performance. [27,28] Additionally, E/Em ratio, an important noninvasive marker of LV filling pressure, has been used increasingly in recent years. [29] It was reported that ROS in CAPD patients without diabetes affected glucose metabolism positively and decreased insulin resistance.…”
Section: Discussionmentioning
confidence: 99%